Immune imbalance mediates the relationship between plasma vitamin D concentration and preeclampsia in Chinese pregnant women: a case–control study - Chen, Huanan; Bo, Yacong; Cao, Yuan; Liu, Jinyan; Nie, Jiaqi; Duan, Dandan; Dou, Weifeng; Zhao, Xianlan; Fu, Wenjun; Zhang, Yi; Liu, Yanhua (Frontiers in Nutrition, 2025)
BackgroundVitamin D insufficiency is associated with an increased risk of preeclampsia. However, the role of T helper cell type 1 (Th1)/Th2 and Th17/regulatory T cell (Treg) balance in this association is unclear.MethodsWe conducted a case–control study to explore the mediating effects of immune balance on the relationship between the plasma vitamin D concentration and preeclampsia. This study included 373 pregnant women recruited between March 2016 and February 2019 (192 cases and 181 controls). The cytokines as well as various T cell subsets were analyzed using ELISA and flow cytometry, respectively. Spearman’s correlation was used to investigate the association between vitamin D and cytokines as well as T cell subsets and mediating analysis was performed to identify the modifying effects of immune balance on this association.ResultsThe Th1/Th2 and Th17/Treg ratios were negatively associated with the plasma concentration of 25-hydroxyvitamin D2 (25(OH)D2). Mediation analysis found that the Th1/Th2 as well as Th17/Treg ratios mediated the effect of 25(OH)D2 on the risk of preeclampsia, the mediating effects accounted for 59.59 and 40.45%, respectively.ConclusionOur results provided preliminary evidence for a potential mediating role of the Th1/Th2 and Th17/Treg balance in the association between plasma 25(OH)D2 and preeclampsia. Keeping higher levels of vitamin D, especially 25(OH)D2 might help maintain the immune balance and decrease the risk of preeclampsia.